2021
DOI: 10.1111/1749-4877.12573
|View full text |Cite
|
Sign up to set email alerts
|

Song variation of a native songbird in a modified habitat by invasive plant

Abstract: Habitat structure has been considered as an important factor affecting the acoustic evolution of birds, and bird songs are increasingly affected by artificial environmental variation. Invasive plants sometimes can dramatically alter native habitats, but the song variation of native songbirds migrating into invaded habitats has received little attention. The invasion of smooth cordgrass Spartina alterniflora in the coastal wetlands of eastern China has drastically altered the vegetation structure and some small… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…In Chongming Dongtan, Shanghai, China, the invasion of Smooth Cordgrass attracted the nonnative species of Marsh Grassbird Helopsaltes pryeri to enter and nest in it, and the reproductive success rate was not lower than that of other primitive habitats (Ma et al, 2011). It has also been recorded in Yancheng, Jiangsu, that the native bird, Plain PriniaPrinia inornata , adapts to and utilises Smooth Cordgrass and enters it and sings during the breeding season (Chen et al, 2022). However, these records and studies are of nonspecialised birds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Chongming Dongtan, Shanghai, China, the invasion of Smooth Cordgrass attracted the nonnative species of Marsh Grassbird Helopsaltes pryeri to enter and nest in it, and the reproductive success rate was not lower than that of other primitive habitats (Ma et al, 2011). It has also been recorded in Yancheng, Jiangsu, that the native bird, Plain PriniaPrinia inornata , adapts to and utilises Smooth Cordgrass and enters it and sings during the breeding season (Chen et al, 2022). However, these records and studies are of nonspecialised birds.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that Smooth Cordgrass invaded the coastal areas of China, occupying the bare beach and shrinking the growth space of native vegetation, resulting in the decline of original biodiversity due to changes in the habitat (Yu et al, 2022;Zuo et al, 2012). With the increase in invasion time, it has also been proven that some passerine birds have adapted to live in the invasion (Ma et al, 2011;Chen et al, 2022). However, the existing studies and reports of native birds entering Smooth Cordgrass are report nonspecialised birds, which are widely distributed in different habitats and have strong adaptability.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that smooth cordgrass invaded the coastal areas of China, occupying the bare beach and shrinking the growth space of native vegetation, resulting in the decline of original biodiversity due to changes in the habitat (Yu et al, 2022;Zuo et al, 2012). Some native passerine birds have begun to adapt to invaded habitats; they enter smooth cordgrass and rely on exotic plants for foraging, hiding, flocking, perching and reproduction (Chen et al, 2022(Chen et al, , 2023. This change may be due to the length of time of smooth cordgrass invasion in native habitats (Chen et al, 2019(Chen et al, , 2022.…”
Section: Introductionmentioning
confidence: 99%
“…The shrinkage of native habitats due to smooth cordgrass invasion and human disturbances may drive more birds that rely on native vegetation (Reed, Phragmites australis ) to attempt to use the invaded habitats, although invasive vegetation may be an ecological trap (Chen et al, 2019 ; Ma et al, 2014 ). Previous studies and reports of native birds entering smooth cordgrass focused nonspecialised birds, which are widely distributed in different habitats and have strong adaptability (Chen et al, 2019 , 2022 , 2023 ; Ma et al, 2014 ). Obligate birds are highly dependent on specific habitats due to their narrow niche and, therefore, are more affected by exogenous disturbance (Dehling et al, 2021 ; Jorge et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…We have interesting examples where the changes resulted directly from anthropogenic noise, such as airport noise [ 27 ] or wind farms [ 28 ]. Yet, humans also affect or destroy the natural structure of the vegetation, which directly affects the parameters of sound transmission and the occurrence of other vocally active animal species, which after all, also changes ambient noise [ 29 , 30 ]. Regardless of whether environmental changes are natural or human-induced, they may affect song behaviour and evolutionary diversification [ 31 ].…”
Section: Introductionmentioning
confidence: 99%